Mechanical and tribological characterization of self-lubricating Mg-SiC-Gr hybrid metal matrix composite (MMC) fabricated via mechanical alloying - Al-maamari, Azzat Esam Abdulqader; Iqbal, AKM Asif; Dewan Muhammad, Nuruzzaman (Elsevier, 2020)
This study deals with the fabrication and tribo-mechanical characterization of magnesium (Mg)-silicon carbide (SiC)- graphite (Gr) hybrid metal matrix composites (MMCs). The hybrid MMCs were fabricated by a mechanical alloying process and their mechanical and tribological properties were investigated as well as compared with those of the base material and the Mg-Gr composite. The morphology analysis of the constituent powders and the hybrid powder mixture was conducted through SEM, EDX and XRD. The microstructure of the sintered MMCs showed a uniform distribution of the reinforcement on the matrix. The developed hybrid MMCs exhibited greater mechanical properties when compared to the base material and the Mg-Gr composite. The tribological characterization of the fabricated hybrid MMCs was studied using the pin-on-disc tribometer under dry sliding conditions. The hybrid MMC composed of 5% Gr and 10%SiC (Mgþ5%Grþ10%SiC) demonstrates 92% low wear rate and 53% low friction coefficient than the matrix Mg. Therefore, this hybrid MMC can be a potential candidate to develop components used in the tribological operation.